BIMBINGAN KARIR MELALUI PENDEKATAN CLIENT CENTERED - Erlinda Wati; Nola Nika; Masril Masril (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Education is not only a transfer of knowledge, but also prepares students to plan career options after graduating from high school. Career guidance is solving career problems, obtaining the best adjustment between the abilities and environment of life, obtaining success and self-realization in the course of life, including choosing education and skills to obtain sources of income, which enable a person to progress and develop in quality (standard of living) and quantity (welfare). So the ability of individuals to make decisions related to career issues. Counseling techniques are known as Client-centered Therapy, which is a client-centered therapy technique counseling technique where the role is the counselor himself, the counsellor is left to find his own solution to the problems he is facing. In this paper the researcher tries to analyze and develop about the relationship of career guidance with a client-centered approach to help clients, and the lack of specific references. Researchers try to contribute in terms of guidance and counseling in the development of career guidance with a client-centered approach. The method used in this study is literature research.The results found that client-centered therapy is that clients are given the opportunity to express problems, feelings and thoughts freely. This approach also suggests that a person who has a problem basically still has potential and is able to overcome his own problems in his environment and can make decisions that are meaningful to him and will know the career he designed in the future.